2014
DOI: 10.9790/2380-07151320
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Descriptors in a Morphological Characteristics Considered In Cassava Accessions By Means Of Multivariate Techniques

Abstract: An experiment was conducted to determine the selection of morphological descriptors in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 2 publications
4
12
0
Order By: Relevance
“…In this study, the first two principal components explained 31.18% of the total cumulative variance for the qualitative traits. This result is similar with those of Afonso et al (2014) who found 32.56% of the genetic variance in the first factorial plane. It can also be explained by the fact that the variance distribution is associated with the nature and number of characters used in the analysis and focuses on the first principal components.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the first two principal components explained 31.18% of the total cumulative variance for the qualitative traits. This result is similar with those of Afonso et al (2014) who found 32.56% of the genetic variance in the first factorial plane. It can also be explained by the fact that the variance distribution is associated with the nature and number of characters used in the analysis and focuses on the first principal components.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, aiming at reducing inconsistencies in the elimination of descriptors, the adoption of two procedures is common to indicate the most relevant descriptors. For example, Afonso et al (2014), and Castro et al (2012) employed the same direct selection criteria proposed by Jolliffe (1972Jolliffe ( , 1973 and Singh coeficiente to select morphoagronomic descriptors for Manihot esculenta Crantz and yellow passion fruit, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis are useful tools to identify the more informative and the less relevant descriptors in the characterization and evaluation of a germplasm to be used in genetic improvement programs, since it supplies information to exclude descriptors that represent little contribution to the total variation (Cruz, Carneiro, & Regazzi, 2004). The use of more than one procedure to discard redundant characters has been adopted to provide higher security to the selection of descriptors (Castro, Neves, Jesus, & Oliveira, 2012;Afonso et al, 2014;E. Oliveira, F. Oliveira, & Santos, 2014;Silva, Carvalho, & Duarte, 2013;Silva et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Afonso recently reported an experiment to characterize 200 accessions from EMBRAPA's Cassava Germplasm Active Bank (BAGM, Brazil) using 35 morphological and agronomic descriptors [1]. Importantly, 20 characters are found to be important in the classification of germplasm of manioc, eleven of those being quantitative descriptors and nine qualitative.…”
Section: Resultsmentioning
confidence: 99%